LEGAL AUTHORITY AND HUMAN RIGHTS BOUNDARIES IN MILITARY POLICING: NAVIGATING THE DUAL MANDATE OF DISCIPLINE ENFORCEMENT AND CIVIL PROTECTION - Deni Iqbal; Hendro Wijiantoro; Indriani MR Hutagalung; Nina Anis (Cognitionis Civitatis et Politicae, 2026)
Military policing operates at the intersection of disciplinary authority and civilian engagement, creating complex tensions between enforcement mandates and human rights obligations in contemporary security environments. Expanding roles in peacekeeping, internal security, and hybrid operations have exposed gaps in legal clarity and accountability mechanisms. This study aims to examine how legal authority is defined and applied in military policing and how human rights boundaries are maintained under dual mandates. A qualitative doctrinal and socio-legal approach was employed, combining analysis of legal instruments, comparative frameworks, and secondary operational data across jurisdictions. Findings indicate that while disciplinary authority is comprehensively regulated, civilian engagement rules, detention safeguards, and oversight mechanisms remain inconsistently defined. Policy coherence, institutional oversight, and training significantly influence compliance with human rights standards, while legal ambiguity increases reliance on discretion and risk of violations. The study concludes that effective military policing requires harmonized legal frameworks, explicit operational guidelines, and strengthened accountability systems to balance authority with rights protection. Integration of legal clarity and institutional capacity is essential for ensuring consistent and rights-compliant practice in evolving security contexts.